Chemical absorption of CO2 in alkaline solutions using an intensified reactor. (10th May 2022) - Azizi, Fouad; Kaady, Lynn; Al‐Hindi, Mahmoud
Abstract: Capturing carbon dioxide (CO2 ) emissions from point sources is critical for a sustainable chemical industry. Several techniques have already been developed and the race is ongoing to meet more stringent limitations at lower operating costs. This study presents the capability of a novel, flexible reactor to achieve high absorption rates at very low power consumption. CO2 absorption in an aqueous sodium hydroxide (NaOH) solution was used as a benchmark. An air–CO2 stream made of 30% v/v CO2 was injected co‐currently with the aqueous alkaline solution in a tubular reactor equipped with woven mesh mixers. The removal efficiencies were measured along the length of the reactor, which operated at total mean flow velocities ranging between 1–2 m/s and gas phase holdups between 10%–30%. Four different mixer geometries were also tested, and the results were analyzed based on the operating conditions and reactor design configurations. While these studies can be further optimized and potentially applied in carbon capture operations, it was found that more than 96.5% of the CO2 could be removed using different combinations of mixer geometry and operating conditions. This high removal efficiency was reached within a residence time of 400 ms at a low cost of 23.65 kWh / t C O 2 .